Peran Guru Dalam Menerapkan Kebersihan Diri Pada Anak di TK Negeri Pembina Keliling Danau - Ogemi, Penia Lisa; Eliza, Delfi (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2022)
Cleanliness is a very important thing to pay attention to, especially personal hygiene in early childhood. Because at an early age children experience a process of rapid growth and development, cleanliness is the main thing that must be considered because children are very susceptible to disease. This requires teachers to be able to apply personal hygiene to children. This study aims to describe the teacher's role in implementing personal hygiene in children. The Pembina Keliling Danau State Kindergarten became the research subject, namely one principal and seven  teachers. The use of qualitative analysis in this study with observation, interviews and documentation techniques as data collection. The result of the research is that the teacher motivates children in terms of maintaining cleanliness, providing guidance and praise to children. As well as the use of varied and interesting media also involve children in the activities carried out.